Jurisprudential Welfare Through the Transformation of the “Rendang-Mu” Qurban Meat Management System - Hayati, Mardiyan; Budiman, Mamdukh; Wijaya, Mirza Mahbub; Masuwd, Mowafg (Fakultas Agama Islam, Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to explore the values of benefit from the perspective of Islamic law regarding the transformation of qurban meat management through the Rendang-Mu program within the Lembaga Amil Zakat Infaq Shadaqah Muhammadiyah (LAZISMU) in the Central Java region, Indonesia. The research employed a descriptive qualitative approach. Data collection techniques involved snowball and purposive sampling, with analysis conducted using the maqasid al-Shariah theory by al-Shatibi. The findings indicate that the Rendang-Mu Program represents a transformation in the pattern of meat management and distribution, implementing a system of qurban meat management through canning and packaging with three essential benefits that facilitate and enhance its utility: (1) prolonged consumption and distribution over an extended period, (2) practical, delicious, and nutritious, (3) more evenly distributed reach, (4) high flexibility in achieving community food security, and (5) compliance with Islamic law.